The investigations of bioactive copper(II) complexes with reduced low-molar dextran. Issue 2 (2008) - Cakić Cakić, Milorad Milorad; Mitić Mitić, Žarko Žarko; Nikolić Nikolić, Goran S. Goran S.; Ilić Ilić, Ljubomir Ljubomir; Nikolić Nikolić, Goran M. Goran M.
Abstract : The optimization of the reaction conditions (pH, T, t ) to obtain stable copper(II) ion complexes with dextran derivatives were investigated in this paper. A complete synthesis of stable aqueous complexes can be realized with reduced low-molar polysaccharides, at an average molar mass 5000 g mol –1 and pH 7.5–8. Fourier-transform IR spectra of polysaccharide dextran and its compounds with copper(II) ion, recorded at room temperature, were analyzed in order to obtain the information about the structure and the conformation of these polymer compounds. The ESR parameters of the spectra indicate the square-planar coordination of Cu(II) ion with four O atoms. Copper(II) complex formation with dextran and its derivatives were analyzed by physicochemical methods. Synthesized complexes of Cu(II) ion with reduced low-molar dextran in comparison with commercial preparations showed the considerably lower acute toxicity (LD 50 1705).